Personal adaptation in the elderly : A field study in the Kurdistan Region/Iraq - محمد نورى عبداللە, عادل; نامق صابر, نيان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Psychological adjustment is one of the active subjects in the field of psychology, because if we don’t build aware and mentally stable people, we can’t build a healthy society. This research attempts to present the psychological adjustment of the elderly from the dimension of personal adjustment. The objective of this study is demonstrating the personal adjustment of the elderly according to (age, gender, education and marital status). The research was conducted using an analytic survey which is a method of social survey. The sample of the research consisted of elderly residents of the Iraqi Kurdistan Region. The results of the study show that personal adjustment among the elderly is high and does not change with age, and male elders have a higher personal adjustment level than female elders and personal adjustment increases with a higher educational level. Older people who are married have more personal adjustment more than older people who are divorced or whose spouses have died.